Gendered Impacts of Crises and Pandemics - Quisumbing, Agnes R. (2020)
Agnes Quisumbing POLICY SEMINAR Virtual Event - What do we need for a gender-sensitive Covid-19 response in agriculture and food security? Insights from research and practice MAY 21, 2020 - 09:30 AM TO 10:45 AM EDT